Identification of Secondary Metabolites in Ethyl Acetate Extract of Ki Encok Plant Roots (Plumbago zeylanica Linn) and In Silico Cytotoxicity Activity - Purwoko, Mitayani; Mundijo, Trisnawati; Astri, Yesi; Rohani, Siti (Departemen Kimia, 2025)
The Ki Encok plant (Plumbago zeylanica Linn) has been extensively studied and is known to have cytotoxic activity. However, no research has yet investigated the compound content of the ethyl acetate extract from that plant. This study aims to identify the secondary metabolite content in the ethyl acetate extract of Plumbago zeylanica L. roots and to determine the potential of these secondary metabolites to bind with the Caspase-3 protein in silico. The ethyl acetate extract of Plumbago zeylanica roots was tested for its phytochemical properties and examined using GC-MS. The compounds found were then searched for their structures in Pubchem, tested in silico using the CB-Dock2 software, and evaluated for drug-likeness with SwissADME. Qualitative phytochemical tests indicate the presence of alkaloid and tannin compounds. The GC-MS test showed the presence of Plumbagin, Gamma sitosterol, and 4-ethoxybenzaldehyde. In the in silico test, docking between Gamma sitosterol, Plumbagin, and 4-ethoxybenzaldehyde with the target protein Caspase-3 has free binding energies of -8.5, -7.0, and -6.1. The Gamma sitosterol-Caspase-3 complex shows the best free-binding energy among the three ligands. Further in vitro or in vivo studies are needed to assess whether the interaction between Gamma sitosterol and Caspase-3 is inhibition or activation.